The 1995 Australian workplace and industrial relations survey (AWIRS 95) : an OHS perspective - Mitchell, Rebecca; Mandryk, John (National Occupational Health and Safety Commission, 1998)
"This analysis of the 1995 Australian Workplace and Industrial Relations Survey (AWIRS 95) is an initiative of the National Occupational Health and Safety Commission to produce more detail information on OHS. The main AWIRS 95 survey provided a general picture of work relations in Australia and included some information on OHS. This NOHSC analysis from an OHS perspective should complement the broad overview presented in the major publication "Changes at Work: The 1995 Australian Workplace Industrial Relations Survey" The injury and illness experience of employees reported in the survey was based on self reports and can be used to complement information obtained from the workers’ compensation based National Data Set. The authors wish to acknowledge the assistance of Tim Driscoll (Epidemiology Unit), Tim Williams and the Statistics Unit and other NOHSC staff who have commented on various drafts of this report. The authors also wish to acknowledge the original investigators and authors of the publication "Changes at Work: The 1995 Australian Workplace Industrial Relations Survey" (the original investigators bear no responsibility for this analysis and interpretation of the AWIRS data) and also the Social Science Data Archives who made the AWIRS data available to NOHSC."